KEEFEKTIFAN KALIMAT DALAM TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 1 TANJUNG RAYA - Nurminto, Toto; Afnita, Afnita (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is threefold, namely (1) the effectiveness of the sentence in the exposition essay of VIII grade students of SMP Negeri 1 Tanjung Raya in terms of sentence structure, (2) choice of words, and (3) spelling use. The type of research used is qualitative research using descriptive methods. Data of research is the results of identification of sentence ineffectiveness used in essays of exposition and sourced from the object of research. The technique of validating the data used is the thick description technique. Data were analyzed using simple statistical descriptive techniques and qualitative analysis using formats. Of 264 sentences used as research data, there were 47 effective sentences and 199 sentences were not effective. This means that there is still a lack of understanding of VII grade students of SMP Negeri 1 Tanjung Raya about effective sentences in exposition essays. The ineffectiveness of these 46 sentences is because they do not meet one or more of the indicators used in this study. Second, 42 sentences are not effective in terms of sentence structure. this is because one element is incomplete. Third, 125 sentences are not effective in terms of the use of word choices. This is due to inappropriate choice of words. Fourth, 97 sentences are not effective in terms of spelling usage. 48 sentences on the inaccuracy of the use of capital letters, 5 sentences on the inaccuracy of the use of dots, and 44 sentences on the inaccuracy of using commas. Kata kunci: Keefektifan, Kalimat, Teks Eksposisi